International governance through soft law: The case of the OECD transfer pricing guidelines - Alberto Vega (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2012)
Soft law plays an important role in the regulation of international tax matters. This paper focuses on the case of the OECD Transfer Pricing Guidelines and analyses the relationship between this non-binding instrument and the formal sources of law. From the perspective of international law, the OECD Guidelines are mainly connected to double tax treaties, but they may also influence customary norms and the general principles of law. From the point of view of domestic legal systems, references to the OECD Guidelines can be found in the tax legislation of some countries and, especially, in the interpretative circulars of the Tax Administrations. Furthermore, in some states the courts have also taken the OECD Guidelines into account in their judgements, which shows that they are almost treated as hard law. However, this practical relevance of the Guidelines does not seem to be in accordance with the process in which they were made in the OECD, which could be more open to the different stakeholders and more transparent. – – Soft Law spielt eine bedeutende Rolle in der Regulation internationaler Steuerangelegenheiten. Das vorliegende Arbeitspapier konzentriert sich auf die OECD-Richtlinien für Verrechnungspreise und analysiert das Verhältnis zwischen diesem nicht bindenden Instrument und den formellen Quellen des Rechts. Aus der Perspektive des Völkerrechts sind die OECD-Richtlinien primär mit Doppelbesteuerungsabkommen verknüpft. Dennoch können diese sowohl Auswirkungen auf das Gewohnheitsrecht als auch auf die allgemeinen Rechtsgrundsätze haben. Aus der Sicht der nationalen Rechtsordnungen finden sich Verweise auf die OECD-Richtlinien in den Steuergesetzen einiger Länder und insbesondere in den interpretativen Rundschreiben von Finanzverwaltungen. Die Berücksichtigung der OECD-Richtlinien durch die Gerichte einiger Staaten weist außerdem darauf hin, dass diese fast wie hard law behandelt werden. Trotzdem scheint die praktische Relevanz der Richtlinien nicht im Einklang mit dem Prozess zu stehen, in dem diese von der OECD geschaffen wurden. Dieser könnte offener für unterschiedliche Interessengruppen sein und mehr Transparenz aufweisen.
Keywords: 300; soft law; transfer pricing; international taxation; OECD; international governance; recommendations; guidelines; Verrechnungspreis; Doppelbesteuerung; Internationales Steuerrecht; Völkerrecht; OECD-Staaten